Goals for Development : History, Prospects, and Costs - Devarajan, Shantayanan; Miller, Margaret J.; Swanson, Eric V. (World Bank, Washington, D.C., 2013)
The Millennium Development Goals set quantitative targets for poverty reduction and improvements in health, education, gender equality, the environment, and other aspects of human welfare. At existing rates of progress many countries will fall short of these goals. However, if developing countries take steps to improve their policies and increased financial resources are made available, significant additional progress toward the goals is possible. The suthors provide a preliminary estimate of the additional financial resources which would be required if countries would work vigorously toward meeting the Millennium Development Goals. Two estimates of the resource gap are developed, one by estimating the additional resources necessary to increase economic growth so as to reduce income poverty, the other by estimating the cost of meeting specific goals in health, education, and the environment. Both estimates yield a figure in the range of $40-$70 billion in additional assistance per year, which is in line with estimates from other international development agencies and which would roughly represent a doubling of official aid flows over 2000 levels. While the authors believe this is a reasonable first approximation of the costs associated with achieving the Millennium Development Goals, it should be interpreted with caution for several reasons, including the lack of empirical data in many countries to estimate the relationship between expenditures on health or education and related outcomes, or the relationship between investment and growth, the sensitivity of the results to changes in the policy environment (both at the macroeconomic and sector level, and with respect to international trade), and opportunities for increased-and more efficient-domestic resource mobilization.